Compressive Strength and Thermal Conductivity of Porous Mullite Ceramics - Muhammad Waziz Wildan; F Marpaung (Departmen Teknik Mesin dan Industri, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Porous ceramics are a form of ceramic material with widespread applications, such as filters, isolators, and acoustics. This research aimed to investigate the compressive strength and thermal conductivity of porous mullite ceramics (3Al2O3.2SiO2 or Si2Al6O13) produced using dry yeast powder as a PFA (pore-forming agent). Kaolin powder (Al2O3.2SiO4.2H2O or Al2Si2O5(OH)4) was used as a raw material for producing mullite ceramics. Kaolin powder and dry yeast powder were mixed at a variety of dry yeast powder weight fractions: 0%, 5%, 10%, 15%, 20%, and 25%. The composition was mixed using Turbula Mixer for 1 hour. The cylindrical green body (diameters of 12 mm, 15 mm, and 30 mm) of every constituent was formed by the uniaxial pressing method at 10 MPa. Monolithic kaolin was sintered at variable temperatures (1,100 oC, 1,200 oC, 1,300 oC, 1,400 oC, 1,450 oC) for 2 hours then subjected to several tests for its density. From the bulk density tests, it was found that the optimum temperature for 2-hour sintering was 1,450 oC. This temperature was then used for the sintering process of the kaolin specimens which contained dry yeast powder. Testing was performed on the microstructure, bulk density, burning waste in mass and volume, compressive strength, and thermal conductivity. According to the literature, kaolin will transform into mullite (3Al2O3.2SiO2 or Si2Al6O13) and cristobalite (SiO2) at 1,450 oC. It was found that with the increase in the content of dry yeast powder as PFA in the mixture with kaolin, the bulk density decreased (from 2.44 gr/cm3 to 1.521 gr/cm3), the porosity increased (from 23.77% to 52.48%), the compressive strength decreased (from 38.04 MPa to 4.51 MPa), and the thermal conductivity decreased (from 3.76 W/moC to1.34 W/moC), each from yeast powder content 0% to 25%.